Estrategias de Marketing en el Comercial “Don Marturo” del Cantón Vinces - CERVANTES BURGOS, DIEGO MICHAEL (2018)
he commercial "DON MARTURO" located in the canton of Vinces that is located in the streets 10 DE AGOSTO # 209 and BALZAR next to the Comercial Artefacta. Start your business activities May 28, 1992 founded by Mr. Wilfrido Desiderio López, today his owners are his children Marjorie Janeth Desiderio Peralvo and Javico Desiderio Peralvo, whose business is wholesale and retail sales of stationery products of pharmacies and retail sales of general bazaar items. The aforementioned products are sold to the population of Vinceña and the sectors close to this city, offering products of different brands and quality; whose purpose is to satisfy the needs of a highly demanding market.